PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI - Maulidia Adinda Pramesti; Uswatun Chasanah (LP2M Universitas Bina Bangsa, 2021)
This research aims to find out product quality and price to customer loyalty with consumer satisfaction as a mediation variable at Pondok Bakaran Giwangan Yogyakarta. Quantitative research, the data used is primary and secondary data with a sample of consumers who have bought (at least 1 time) the food and beverage menu of Pondok Bakaran Giwangan Yogyakarta amounting to 100 samples. Purposive sampling technique. The data analysis technique in this study is Partial Least Square using the SmartPLS 3.3.3 application. The results of this study showed that: (1) Product quality had a positive effect on consumer satisfaction with a significance value of 0.019 <0.05 (2) Product quality had no positive effect on consumer loyalty with a significance value of 0.127 >0.05 (3) Price had no positive effect on consumer satisfaction with a significance value of 0.068 >0.05 (4) Price had no positive effect on consumer loyalty with a significance value of 0.068 >0.05 (4) Price had no positive effect on consumer loyalty with a significance value of 10.068 >0.05 (4) Price had no positive effect on consumer loyalty with a significance value of 0.068 >0.05 (4) Price had no positive effect on consumer loyalty with a significance value of 0.068 >0.05 (4) Price had no positive effect on consumer loyalty with a significance value of 0.068 >0.05 (4) Price had no positive effect on consumer loyalty with significance value of 0.068 >0.05 (4) Price had no positive effect on consumer loyalty with significance value of 0.068 >0 0.162 >0.05 (5) Consumer satisfaction positively affects consumer loyalty 0.014 <0.05 (6) consumer satisfaction does not mediate the effect of product quality on consumer loyalty with a significance value of 0.127 >0.05 (7) consumer satisfaction does not mediate the effect of price on consumer loyalty with a significance value of 0.119 >0.05. The results of the calculation of the value of R2 consumer satisfaction 0.238 and consumer loyalty 0.299.